Politik, Publik Figur, dan Generasi Muda: Analisis Strategi Komunikasi Politik Verrell Bramasta Sebagai Representasi Anak Muda dalam Pemilu 2024 - Azhar, Chantika Felicia; Adrian, Muhammad Farel; Apriliana, Nurul Alifah Putri; Mimirawati, Sekar; Aji, Muhammad Prakoso (Metta : Jurnal Ilmu Multidisiplin, 2025)
This study analyzes Verrell Bramasta's political communication strategy in the 2024 elections as a representative of the younger generation through a descriptive qualitative approach with a focus on digital communication patterns on TikTok and Instagram. The results show that Verrell Bramasta utilizes personal narratives, symbolic visuals, and an emotional style combined with agenda setting and Push, Pull, Pass Marketing strategies to build an image of a young politician relevant to Generation Z and millennials. This strategy shows a shift from an elite political communication model to a more personal and emotional form based on social media. However, the effectiveness of this strategy is still limited by the lack of political substance and two-way interaction. Academically, this study contributes to the understanding of the transformation of public figures' digital political communication and its implications for the patterns of political engagement of the younger generation in Indonesia.